IMPLEMENTASI MODEL JUCAMA BERBANTUAN GEMAS TERHADAP KEMAMPUAN BERFIKIR KRITIS SISWA SMP - Masyuda, Lida; Lukman, Hamidah Suryani; Nurcahyono, Novi Andri (Universitas Bhinneka PGRI, 2025)
This study aims to compare students' critical thinking abilities by implementing the JUCAMA learning model assisted by GEMAS for junior high school students. The research method is quantitative, using a quasi-experimental design with a Control Group Pretest and Posttest Design. The population in this study consists of all students from SMPN 12 Kota Sukabumi in the eighth grade during the odd semester of the 2024/2025 academic year, totaling 229 students. A sample was taken from the population of all eighth-grade students at SMPN 12 Kota Sukabumi using cluster random sampling. This, the sample for this study consists of 88 eighth-grade students from SMP Negeri 12 Kota Sukabumi, divided into two experimental classes and one control class. The data analysis technique used is ANOVA with a significance level of α=5%. This research employs an instrument for testing students' critical thinking abilities in the form of pretest and posttest questions, as well as non-test instruments such as observation sheets and documentation. The results of this study indicate that the JUCAMA model assisted by GEMAS is more effective than both the JUCAMA model and Discovery Learning in enhancing the critical thinking abilities of junior high school students.